Web and wireless geographical information systems : 11th International Symposium, W2GIS 2012, Naples, Italy, April 12-13, 2012. Proceedings - Peron, Adriano; Tezuka, Taro; Martino, Sergio (Lecture Notes in Computer Science, 2012)
This book constitutes the proceedings of thw 11th International Symposium on Web and Wireless Geographical Information Systems, W2GIS 2012, held in Naples, Italy, in April 2012. The 13 full and 4 short papers presented in this book were carefully reviewed and selected from 32 submissions. The papers are organized in topical sections names: 3D and multimodal spatial interaction; positioning; spatial human-computer interaction; trajectory analysis; geo semantics; and sensor networks.